NATIONAL MINORITIES IN GEORGIA: PROBLEMS OF DEFINITION AND LEGAL STATUS - SVANIDZE, Guram (CENTRAL ASIA AND THE CAUCASUS, 2006)
Georgia has long failed to give its due attention to the problem of national minorities. The academic and legislative aspects of the problem are underdeveloped because of the inadequate conceptual system and lack of definition of the term “national minority.” This topic has always been considered perilous in the political sense and is known to arouse unhealthy restlessness in society.The official structures justified the delay in ratification of the Framework Convention on the Protection of National Minorities, among other things, by the lack of consensus on definition. The Georgian Parliament’s resolution on ratification of the above-mentioned Framework Convention (13 September, 2005, No.1938-II s) was the first attempt to introduce clarity into this issue at the official level. The document gives a definition of minority, but experts expressed their dissatisfaction with the formulation proposed. This criticism boiled down to the fact that the definition was much too narrow: it applied only to compactly residing minorities. The emphasis was essentially placed on Azeris and Armenians densely residing in Lower Kartli and Javakhetia. In addition to everything else, the resolution does not take into account the parameters of “compact residence.” So it was declared that the definition was preliminary and would undergo further polishing.The delicacy of the topic can partially be explained by the fact that our society has long been in the grips of so-called ethnonational thinking. Today we are going to have to get rid of the understanding of the key term “national minority” “successfully” used by Soviet ideologists. In particular, this concept defined a minority as part of an ethnic nation which has its own statehood, or as an ethnic nation which lives in a particular country, is a numerically small group, and does not have its own forms of statehood. Equating statehood with an ethnonational community led to the confusion in terminology.1Our experience of talking to members of minority groups has shown that many of them are dissatisfied with the term “minority.” There are various reasons for this attitude. There is a viewpoint that says treatment of all the state’s citizens should be based on the principles of equality. According to this category of people, being defined as a minority insults their sense of civilian dignity. This kind of interpretation is the first sign of civilian patriotism, an approach in which even the theoretical presupposition that Abkhazians and Ossetians living within the autonomies are minorities is a vestige of ethnonational thinking and arouses their protest. For example, only those Ossetians who live beyond the boundaries of the autonomies belong to minorities. The Armenians living in Javakhetia, the Azeris from Lower Kartli, and so on, are not particularly enthusiastic about this term. Expressions such as the following, “There is the Azeri nation, and we are a part of it,” are more characteristic of cases when a more “sincere” form of manifesting the ethnonational mentality exists. Certain governing laws can be traced: the more compactly a minority resides, the closer its geographical ties with its historical homeland (Lower Kartli, Javakhetia), and the more political attributes there are in the self-government regions (Abkhazia and South Ossetia), the less desire the community members have to be considered a minority